Facilitating Sounds in Indonesian - Isodarus, Praptomo Baryadi (Universitas Sanata Dharma, 2018)
This article presents the research result of facilitating sounds in Indonesian. Facilitating sound is a sound which facilitates the pronunciation of a sound sequence in a word. Based on the data analysis, the facilitating sounds in Indonesian are [É™], [y], [w], [Ê”], [m], [n], [á¿ƒ], [Åˆ] and [á¿ƒÉ™]. Sound [É™] facilitates the consonant cluster pronunciation in a word. Sound [y] facilitates the pronunciation of the sound sequences [ia] and [aia] among syllables and morphemes. Sound [w] facilitates the pronunciation of sound sequence [ua] among syllables and morphemes and the sound sequence of [oa] and [aua] among morphemes. Sound [Ê”] facilitates the sound sequence [aa] among syllables and morphemes and the sound sequence [oa] among syllables. Sound [m] facilitates the pronunciation of nasal sound sequence [N] in prefixes me(N) â€“ or pe(N)- whose morpheme base begins with sounds [b, p, f, v]. Sound [n] facilitates the pronunciation of sound sequences [d] and [t] in the beginning of the morpheme base. Sound [á¿ƒ] facilitates the pronunciation of sound sequence [N] in prefixes me(N) â€“ or pe(N)- whose morpheme base begins with the vowels [a, i, u, e, Ó™, Ô‘, o, á´], [g], [h] and [k]. Sound [Åˆ] facilitates the pronunciation of sound sequence [N] in prefixes me(N) â€“ or pe(N)- whose morpheme base begins with sounds of [j, c, s]. Sound [á¿ƒÉ™] facilitates the pronunciation of words which are formed by prefixes me(N) â€“ or pe(N)- with one syllable morpheme base.Â Keywords: facilitating sound, phonology, Indonesian